PARAOXONASE ACTIVITY AND PON1 (Q/R192) GENE POLYMORPHISM IN ISCHEMIC STROKE PATIENTS: Life Science-Genetics - MUGUNDAN MURUGAN, MAGESH; ALAGIRISAMY, RENUKA; MANOKARAN, SHARMILA; BALAKRISHNAN, ANANDAN (International Journal of Life Science and Pharma Research, 2012)
Background: Paraoxonase (PON1) has two polymorphisms Q/R192 and L/M 55 associated with ischemic stroke. The effect of Q/R192 PON1 variants, its activity, and lipid profile in ischemic stroke were studied in South Indians. Design and Methods: The PON1-Q192R polymorphism, serum PON1-ARE activity and lipid profile were analyzed in 308 ischemic stroke patients and in 330 age and sex matched controls. Results: R allele frequency of the codon 192 polymorphism was higher in ischemic stroke cases when compared with controls. Odds ratio of the cases with RR + QR genotype versus QQ genotype was 1.67 (P < 0.01). Patients with ischemic stroke cases with QQ, QR, RR genotypes had highly significant LDL (P < 0.01) and HDL cholesterol (P < 0.01). Conclusion: Our data suggested that there was a significant association between PON1 activity, and PON1-Q192R genotypes in ischemic stroke in South Indians.